Genotypic and phenotypic characteristics of Escherichia coli involved in transfusion‐transmitted bacterial infections: implications for preventive strategies. Issue 8 (10th September 2018) - Desroches, Marine; Clermont, Olivier; Lafeuillade, Bruno; Rodriguez, Christophe; Darty, Mélanie; Royer, Guilhem; Bouvet, Odile; Ounnoughene, Nadra; Noizat‐Pirenne, France; Denamur, Erick; Decousser, Jean‐Winoc
Abstract : BACKGROUND: Transfusion‐transmitted bacterial infections (TTBIs) are the main residual infectious complications of transfusions. Escherichia coli and platelet (PLT) concentrates may be epidemiologically associated, leading to severe, if not lethal, TTBIs. We investigated the genotypic and phenotypic reasons for this clinically deleterious combination. STUDY DESIGN AND METHODS: We investigated a French national E. coli strain collection related to six independent episodes of TTBIs. Their phenotypic characterizations included antibiotic susceptibility testing, growth testing under different culture conditions, serum survival assays, and virulence in a sepsis mouse model. Their genotypic characterizations included polymerase chain reaction phylotyping, whole genome sequencing, and a subsequent in silico analysis. RESULTS: We highlighted a selection process of highly extraintestinal virulent strains, mainly belonging to the B2 phylogroup, adapted to the hostile environment (high citrate concentration and a bactericidal serum effect) of apheresis‐collected platelet concentrates (PCs). Compared to controls, the E. coli TTBI strains grew faster in the PCs due to a superior ability to capture iron. The in vitro growth performances were highly compatible with blood‐derived product real‐life conditions, including storage conditions and delays. The consistent serum resistance of TTBI strains promotes their survival in both the donor's and the receiver's blood and in the PCs. CONCLUSION: This study pointed out that E. coli strains responsible for TTBI exhibit very specific traits. They belong to the extraintestinal pathogenic phylogroups and have a high intrinsic virulence. They can be resistant to complement, capture iron, and grow in the apheresis‐collected PCs. These findings therefore support the reinforcement of the postdonation information.